RENEWABLE ENERGY SOLUTION: SOLAR PHOTOVOLTAIC SYSTEM DESIGN FOR SUPPLYING REMOTE TERMINAL UNIT PANELS IN THE KEDUNG PUTRI IRRIGATION SYSTEM - Handoko Rusiana Iskandar; Laili Fadihilah; Ahmad Daelami (Jurnal Media Elektrik, 2025)
The Kedung Putri Dam Irrigation Area is situated in the Purworejo Regency, Central Java Province. It is an irrigation system employed for agricultural production, although it is significantly distant from grid electrical supplies. Photovoltaic (PV) power plants, utilizing renewable energy sources, exhibit an average solar energy potential of 5.041 kWh/m2/day. The PV system was designed in six steps, from data collecting to performance evaluation. The method started with location data, meteorological data (solar irradiation and temperature), and the Remote Terminal Unit (RTU) panel energy consumption. PVsyst 7.2 calculates daily load capacity, size, and number of solar panels depending on local irradiation. This simulation models system performance using environmental conditions and outputs technical specifications, estimated energy production, and solar fraction. Based on the calculations, PVSyst modelling, and this paper's analysis, the following conclusions were obtained to meet the objectives: RTU panels at B.Ks.1, B.Kd.1, B.Kd.3, and B.Kd.7.Tg must have a minimum PV capacity of 300 Wp and a maximum of 450 Wp with 375 Ah; 12 V battery operation. SCC unit with 20 A load current and 600 W nominal operational power (24 V battery) is installed. Preliminary PVsyst software simulations show that the four locations average 415.125 kWh/year. The four locations utilise 400.5 kWh/year and average 71.5% performance. Average solar fraction ratio of four places is 68.5%; energy lost is 184.23 kWh/year. A thorough review of the PV system's performance shows that 300 Wp has a higher PR value than 450 Wp. The PV capacity has an average annual SF value of 0.685 across the four locations, indicating that the solar power system can supply 68.5% of the RTU panels' power, while 31.5% requires other energy sources or more batteries.